(untitled) (International Journal of Engineering and Computer Science, 2014)
Internet has become a very important factor in our day to day life. It is a wide media for communication and exchange of ideas for people staying in any nook and corner of the world. In this paper an idea is proposed to develop a speech interactive system to provide web application services. The main aim is to provide these services to the special ones who are unable to make use of the current system so efficiently. In this proposed work the main focus is on the web applications. It is tedious for the disabled people who are unable to access internet, this system will help them to download news, or even access their mails through speech. The idea is to incorporate several applications like Email Reader/Sender, News, Reader, Web Content, Blog, RSS Reader, Local System File Reader, Text/Document Reader, and Voice Command System. The proposed system provides access to these applications. So that they can be used by disabled people without the use of the hands to develop an interface between the computer and the user. This is an attempt to develop web application through speech interaction.